Kidney Transplantation After Rescue Allocation—the Eurotransplant Experience: A Retrospective Multicenter Outcome Analysis. Issue 6 (4th October 2022) - Assfalg, Volker; Miller, Gregor; Stocker, Felix; van Meel, Marieke; Groenevelt, Tiny; Tieken, Ineke; Ankerst, Donna; Renders, Lutz; Novotny, Alexander; Hartmann, Daniel; Jell, Alissa; Rahmel, Axel; et al.
Abstract : Background: At Eurotransplant (ET), kidneys are transferred to "rescue allocation" (RA), whenever the standard allocation (SA) algorithms Eurotransplant Kidney Allocation System (ETKAS) and Eurotransplant Senior Program (ESP) fail. We analyzed the outcome of RA. Methods: Retrospective patient clinical and demographic characteristics association analyses were performed with graft outcomes for 2422 recipients of a deceased donor renal transplantation (DDRT) after RA versus 25 481 after SA from 71 centers across all ET countries from 2006 to 2018. Results: Numbers of DDRTs after RA increased over the time, especially in Germany. RA played a minor role in ESP versus ETKAS (2.7% versus 10.4%). RA recipients and donors were older compared with SA recipients and donors, cold ischemia times were longer, waiting times were shorter, and the incidence of primary nonfunction was comparable. Among ETKAS recipients, HLA matching was more favorable in SA (mean 3.7 versus 2.5). In multivariate modeling, the incidence of graft loss in ETKAS recipients was reduced in RA compared with SA (subdistribution hazard ratio, 0.80; 95% confidence interval [0.70-0.91], P  < 0.001), whereas other outcomes (mortality, death with functioning graft (DwFG)) were not significantly different. None of the 3 outcomes were significantly different when comparing RA with SA within the ESP program. Conclusions: Facing increased waiting times and mortality on dialysis due to donor shortage, this study reveals encouragingly positive DDRT outcomes following RA. This supports the extension of RA to more patients and as an alternative tool to enable transplantation in patients in countries with prohibitively long waiting times or at risk of deterioration. Abstract :